A functional analysis of distal biceps tendon repair: single-incision Endobutton technique vs. two-incision modified Boyd–Anderson technique. Issue 1 (2nd January 2016) - Cohen, Steven B.; Buckley, Patrick S.; Neuman, Brian; Leland, J. Martin; Ciccotti, Michael G.; Lazarus, Mark
Abstract: Introduction : The optimal surgical technique for a distal biceps tendon rupture repair still remains controversial. Current biomechanical evidence shows Endobutton fixation to have the highest load-to-failure testing, but clinical results of this are limited. The purpose of this study was to compare patient-oriented functional outcome between a modified Boyd–Anderson two-incision technique and repair with a single-incision Endobutton technique. Methods : All patients who underwent distal biceps tendon repair with a two-incision or Endobutton technique between 2000 and 2010 with two-year follow-up at our institution were identified. Their clinical, operative, and follow-up data was collected and analyzed. The primary outcome was a patient-oriented functional outcome measure (Disabilities of the Arm, Shoulder, and Hand: DASH). Secondary outcomes were evaluated using a subjective questionnaire. Results : Thirty-three patients were repaired with the two-incision technique and twenty-five patients had a repair with a single incision Endobutton technique. All patients receiving the two-incision repair were male, while there were 2 females who had an Endobutton procedure. There was no significant difference between the two-incision and the Endobutton groups in regards to mean DASH score (6.31 versus 5.91, p = 0.697), mean Work DASH score (10.49 versus 0.93, p = 0.166), and mean Sports DASH score (10.54 versus 9.56, p = 0.987). Regardless of technique, most patients were "extremely satisfied" (n = 42, or 72.41%) or "satisfied" (n = 10, or 17.24%) postoperatively, and returned to pre-operative activity in approximately 6 months (6.87 months versus 6.82 months, respectively) (p = 0.457). There was no significant difference in the prevalence of complications (39.39% versus 32.0%, respectively for two incision versus single incision) (p = 0.594). Conclusion : Patients from both surgical groups were satisfied with their post-operative function and had similar functional outcomes and complication rates. Both surgical techniques for distal biceps tendon repair are effective and are similarly safe methods of treatment.